1986
DOI: 10.3739/rikusui.47.101
|View full text |Cite
|
Sign up to set email alerts
|

Age-scaling for the uppermost clayey layer in the 1,400m -core sample from Lake Biwa. A preliminary study.

Abstract: Age-scaling is attempted using the vertical profile of bulk density of the uppermost clayey layer (240-250 m in thickness) in a new deep core sample from Lake Biwa. At first, the empirical porosity-depth relation is physically examined on the basis of a consolidation theory. The vertical profile of bulk density in the upper 180 m of the clayey layer is approximately described by the empirical bulk density-depth relation, which is derived from the porosity-depth relation. By applying the age by fission-track da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…High percentages in the 300-450 m layers are due to the low concentrations of total carbon and those in the 650-804 m layers are probably due to special sedimentary conditions holding organic compounds intact as estimated from relative compositions of lipid compounds such as fatty acids, alcohols, Chlorophyll-like substances in the same core have also been determined by the authors (Ogura et al, 1985) and the variation of the ratios of chlorophyll-like substances to chloroform extractable carbon is consistent with that of paleotemperature estimated by pollen analyses. Recently the authors have found the variation of the ratios concerning chlorophyll-like substances with ages of the core sample determined by Taishi et al (1986), is consistent with the Milankovitch climate cycle during 0.6 million years, though some exceptions are present. The minimum temperature layers found in the study of chlorophylllike substances also appeared in the variation of percent carbohydrate carbon, for example, 50-58 m (0.10-0.12 m.y.…”
Section: Introductionsupporting
confidence: 54%
“…High percentages in the 300-450 m layers are due to the low concentrations of total carbon and those in the 650-804 m layers are probably due to special sedimentary conditions holding organic compounds intact as estimated from relative compositions of lipid compounds such as fatty acids, alcohols, Chlorophyll-like substances in the same core have also been determined by the authors (Ogura et al, 1985) and the variation of the ratios of chlorophyll-like substances to chloroform extractable carbon is consistent with that of paleotemperature estimated by pollen analyses. Recently the authors have found the variation of the ratios concerning chlorophyll-like substances with ages of the core sample determined by Taishi et al (1986), is consistent with the Milankovitch climate cycle during 0.6 million years, though some exceptions are present. The minimum temperature layers found in the study of chlorophylllike substances also appeared in the variation of percent carbohydrate carbon, for example, 50-58 m (0.10-0.12 m.y.…”
Section: Introductionsupporting
confidence: 54%
“…Various chronostratigraphical methods have been applied to the Lake Biwa sediment cores. These include tephrochronology (e. g., Hone, 1984), magnetostratigraphy (Torn et al, 1986), radiocarbon dating (Hone et al, 1971), and fissiontrack dating of zircon crystals (Nishimura, 1984;Taishi et al, 1986;Takemura, 1990). However, the results are in poor agreement due partly to problems with dating methods and partly to provisional stratigraphic correlations.…”
Section: Lake Biwa Sedimentsmentioning
confidence: 99%